PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN MAHASISWA PROGRAM PENDIDIKAN DASAR UNIVERSITAS TERBUKA UPBJJ MALANG KELOMPOK BELAJAR AMANAH BLITAR RAYA - Muawanah Muawanah; Arisyahidin Arisyahidin; Sumardji Sumardji (Universitas Islam Kadiri, 2019)
This study aims to determine the quality of service to student satisfaction Basic Education Program Open University UPBJJ Malang Group of Learning Amanah Blitar Raya. This study was conducted using a quantitative method involving 234 samples from 565 total population. Determination of the quantity of samples using Slovin formula with proportional random sampling technique. The result shows the level of student satisfaction on academic services in tutorial activities on Tangible and Empathy factors have a significant effect on student satisfaction. Researchers recommends to improve the quality of service, especially in the both dimension.